The effects of Social Networking Sites on Brand Benevolence - Langaro, D.; Salgueiro, M.F.; Rita, P. (46th Annual Conference of the European Marketing Academy, 2017)
Social Networking Sites (SNS) like Facebook have been increasingly incorporated in companies´ communication plans, with brands launching their brand pages to communicate directly with their target audiences. Previous studies had validated the positive effects of SNS on brand equity and relationship constructs. The current study extends the analysis to brand benevolence. It evaluates the effects of users´ participation in brand pages on perceived brand benevolence. In the context of brand pages, companies deliver free benefits associated to information sharing, concealing, entertainment and socialization. While doing that they communicate intentions to help and ´do good´ to the consumer, going beyond what is formally expected in a traditional commercial transaction. Previous studies support that when consumers perceive brands´ intentions to help and ´do good´, a sense of brand altruism is generated, with impact on brand benevolence. A sample of 258 valid responses was obtained. The results validate the positive influence of users´ participation on perceived brand benevolence and distinguish the results among users´ different patterns of participation. The study offers theoretical and managerial contributions.